Indirect Organogenesis and Somatic Embryogenesis of Pineapple Induced by Dichlorophenoxy Acetic Acid - Roostika, Ika; Mariska, Ika; Khumaida, Nurul; Wattimena, Gustaaf A (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2012)
ABSTRACTIndirect Organogenesis and Somatic Embryogenesis ofPineapple Induced by Dichlorophenoxy Acetic Acid. IkaRoostika, Ika Mariska, Nurul Khumaida, and Gustaaf A.Wattimena. This research aimed to study the effect of 2,4-D,AdS, and basal media to the regeneration of pineapplethrough indirect organogenesis and somatic embryogenesis,and to study the complete event of somatic embryogenesis.Callus formation was induced by 21, 41, and 62 Î¼M 2,4-Dwith addition of 9 Î¼M TDZ. The non embryogenic calli weretransferred onto 4.65 Î¼M Kn containing medium.Embryogenic callus formation was induced on MS or Bacbasal media consisted of N-organic compounds withaddition of AdS (0, 0.05 and 0.1 Î¼M). The embryogenic calliwere regenerated on modified MS medium with addition of0.9 Î¼M IBA, 1.1 Î¼M BA, 0.09 Î¼M GA3 or MS mediumsupplemented with 0.018 mM BA. The result proved that thesingle auxin of 2,4-D was not enough to induce embryogeniccells. Therefore the non embryogenic calli were regeneratedthrough organogenesis. The 21 Î¼M 2,4-D yielded high level ofcallus formation (80%), higher fresh weight (0.2 g/explant)and higher number of shoot (25 shoots/explant in twomonths). Embryogenic calli were produced on N-organiccompounds enriched media. The regeneration mediumsignificantly affected the level of browning, where the MSmedium with addition of 0.018 mM BA yielded lower level ofbrowning. There was an interaction of embryogenic callusinduction medium and regeneration medium to the numberof mature somatic embryos. The embryogenic callusinduction on MS medium enriched with N-organiccompounds and 0.05 Î¼M AdS followed by the regenerationof somatic embryos on MS medium with addition of 0.018mM BA was the best treatment which yielded 17 maturesomatic embryos/explant